IMPLEMENTASI PROGRAM LISA (LIHAT SAMPAH AMBIL) DALAM MENINGKATKAN KEPEDULIAN LINGKUNGAN SISWA-SISWI DI SDN 007 LONG MESANGAT KABUPATEN KUTAI TIMUR, PROVINSI KALIMANTAN TIMUR - Nurngaini; Siti Maisaroh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Environmental problems in elementary schools are often caused by low student awareness of environmental cleanliness. One effort made to overcome this problem is through the implementation of the LISA (See Trash, Pick It Up) Program. This study aims to describe the implementation of the LISA Program in increasing students' environmental awareness at SDN 007 Long Mesangat. This study uses a descriptive qualitative approach with the research subjects being students and teachers at SDN 007 Long Mesangat. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that the LISA Program is able to increase students' environmental awareness, as demonstrated by changes in student behavior in maintaining school cleanliness, such as disposing of trash in its proper place and picking up trash found in the school environment without being instructed by teachers. The LISA Program also contributes to the formation of a sustainable environmentally conscious character